Zero-Shot Invoice Information Extraction Using Foundation Models with Spatial Prompt Tuning - Ranadheer Reddy Charabuddi (International Journal of Intelligent Systems and Applications in Engineering, 2025)
Extracting structured information from scanned invoices poses significant challenges due to diverse layouts, linguistic variability, and the scarcity of annotated training data. To address this, the study introduces a zero-shot invoice information extraction framework that leverages the Donut foundation model, integrated with spatial prompt tuning. Unlike conventional OCR-based pipelines, the proposed approach operates directly on document images without the need for explicit text recognition or task-specific fine-tuning. The method was evaluated using the SROIE v2 dataset, comprising 973 annotated invoice images, and was implemented using the Python framework. Spatially-aware natural language prompts were used to guide the model’s attention toward relevant regions such as headers or totals. Experimental evaluation demonstrated a notable performance gain, with the model achieving 98.0% accuracy, surpassing baseline methods like BiLSTM-CRF and LayoutLM by over 4%. The results validate the model’s effectiveness and scalability for real-world document automation, especially in zero-shot settings with high template variability. DOI: https://doi.org/10.17762/ijisae.v13i1s.7722